Halogen hydrogen-bonded organic framework (XHOF) constructed by singlet open-shell diradical for efficient photoreduction of U(VI) - Lijuan Feng; Yihui Yuan; Bingjie Yan; Tiantian Feng; Yaping Jian; Jiacheng Zhang; Wenyan Sun; Ke Lin; Guangsheng Luo; Ning Wang (Nature Communications, 2022)
Abstract Synthesis of framework materials possessing specific spatial structures or containing functional ligands has attracted tremendous attention. Herein, a halogen hydrogen-bonded organic framework (XHOF) is fabricated by using Cl− ions as central connection nodes to connect organic ligands, 7,7,8,8-tetraaminoquinodimethane (TAQ), by forming a Cl−···H3 hydrogen bond structure. Unlike metallic node-linked MOFs, covalent bond-linked COFs, and intermolecular hydrogen bond-linked HOFs, XHOFs represent a different kind of crystalline framework. The electron-withdrawing effect of Cl− combined with the electron-rich property of the organic ligand TAQ strengthens the hydrogen bonds and endows XHOF-TAQ with high stability. Due to the production of excited electrons by TAQ under light irradiation, XHOF-TAQ can efficiently catalyze the reduction of soluble U(VI) to insoluble U(IV) with a capacity of 1708 mg-U g−1-material. This study fabricates a material for uranium immobilization for the sustainability of the environment and opens up a new direction for synthesizing crystalline framework materials.